Religion and Support for Democracy: A Comparative Study for Catholic and Muslim Countries - Gu, Man-Li (Politics and religion, 2012)
This article presents a cross-country empirical analysis of the relationship between religion and political attitudes among the Catholic and Muslim publics, using the most recent data from the World Values Survey. We find that public support for democracy is stronger among the better educated in both the Catholic and Muslim countries. Contrary to the conventional belief that pious believers are less receptive to democracy, individual religiosity, measured by belief in God, is found to have a significant positive impact on desire for democracy in both types of society. Our findings further indicate that at the societal level, overt support for democracy is consistently positively correlated to the attachment of a set of more implicit tolerant civil values in Catholic-majority countries, while exactly the opposite is observed in Muslim-majority countries.